2017
DOI: 10.1377/hlthaff.2017.0773
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Bias Toward High-Income-Country Research: A Randomized, Blinded, Crossover Experiment Of English Clinicians

Abstract: Unconscious bias may interfere with the interpretation of research from some settings, particularly from lower-income countries. Most studies of this phenomenon have relied on indirect outcomes such as article citation counts and publication rates; few have addressed or proven the effect of unconscious bias in evidence interpretation. In this randomized, blinded crossover experiment in a sample of 347 English clinicians, we demonstrate that changing the source of a research abstract from a low- to a high-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 30 publications
2
80
0
2
Order By: Relevance
“…Some analyses have found lower success rates for 23 female-authored papers [17,18] and grant applications [19,20], while other studies have found no 24 gender differences in review outcomes (for examples, see [21][22][23][24][25]). Inequities in journal success 25 rates based on authors' nationalities or country of affiliation have also been documented, with 26 reports that authors from English-speaking and scientifically-advanced countries have higher 27 success rates [26,27]; however, other studies found no evidence that the language or country of 28 affiliation of an author influences peer review outcomes [27][28][29]. These inconsistencies could be 29 explained by several factors, such as the contextual characteristics of the studies (e.g., country, 30 discipline) and variations in research design and sample size.…”
mentioning
confidence: 99%
“…Some analyses have found lower success rates for 23 female-authored papers [17,18] and grant applications [19,20], while other studies have found no 24 gender differences in review outcomes (for examples, see [21][22][23][24][25]). Inequities in journal success 25 rates based on authors' nationalities or country of affiliation have also been documented, with 26 reports that authors from English-speaking and scientifically-advanced countries have higher 27 success rates [26,27]; however, other studies found no evidence that the language or country of 28 affiliation of an author influences peer review outcomes [27][28][29]. These inconsistencies could be 29 explained by several factors, such as the contextual characteristics of the studies (e.g., country, 30 discipline) and variations in research design and sample size.…”
mentioning
confidence: 99%
“…Given the known fickleness of citations, including marked group and regional biases, including an unconscious bias towards high‐income country research (Seglen, ; Harris et al . ), citations cannot, and must not, be thought of as a direct measure of either quality or importance and, except at the extremes, are wholly unreliable for assessment of most individual papers and researchers (Casadevall & Fang, ). Indeed, highly cited journals overall have notably high retraction rates (Fang & Casadevall, ), and there is now considerable evidence of systematic bias in citation towards positive findings (Misemer et al .…”
Section: The Top 10 Journals In Physiology Ranked By 2 and 5 Year Immentioning
confidence: 99%
“…Nous nous appliquons à aider de jeunes chercheurs du Sud, parfois peu expérimentés, à se familiariser avec l'exercice normatif et exigeant de la publication scientifique. Les articles rédigés par des scientifiques dont le patronyme renvoie à un pays déshérité ont, nous le savons, moins de chances d'être lus, puis d'être cités par leurs pairs des pays mieux lotis (Harris et al, 2017). Notre revue est en outre tenue de surnager dans un océan hypercompétitif, où les logiques éditoriales, sous-tendues par des logiques commerciales, accordent peu de crédit aux revues scientifiques qui, contre vents et marées, s'attachent à faire valoir la reconnaissance des chercheurs démunis.…”
Section: éDitorialunclassified
“…We make every effort to help young researchers from the South, who sometimes have little experience, to become familiar with the demanding standards of scientific publishing. We know that articles published by scientists whose names evoke a disadvantaged country are less likely to be read and cited by their peers in wealthier countries (Harris et al, 2017). Our journal, moreover, has to sink or swim in a hyper-competitive environment in which editorial lines with an underlying business logic give little credit to scientific journals that persist in battling the odds to gain recognition for disadvantaged researchers.…”
Section: éDitorialmentioning
confidence: 99%
See 1 more Smart Citation